SAT0549 Autologous hematopoietic stem cell transplantation (HSCT) for anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) – a ebmt retrospective survey. (12th June 2018) - Alexander, T.; Samuelson, C.; Daikeler, T.; Henes, J.; Skagerlind, L.; Akil, M.; Ehninger, G.; Jantunen, E.; Farge, D.; Snowden, J.; ,
Abstract : Background: ANCA-associated vasculitides (AAV) are chronic autoimmune diseases, which can present with life-threatening multi-system involvement. Despite the use of rituximab and other available modern biologic therapies some patients with AAV develop severe and refractory courses of disease. Objectives: The aim of this study was to analyse outcomes of autologous hematopoietic stem cell transplantation (HSCT) for refractory AAV Methods: Adults receiving HSCT for AAV and whose data were registered within the EBMT Autoimmune Disease Working Party (ADWP) were identified retrospectively through the EBMT database. Treating physicians were surveyed to produce a retrospective evaluation of outcomes. Results: 7 patients underwent HSCT primarily for AAV between 1999–2014 in 6 centres across Europe. 5 females and 2 males were transplanted; 6 had a diagnosis of granulomatosis with polyangiitis (GPA) and 1 eosoniphilic granulomatosis with polyangiitis (EGPA). Median age was 39 years (range 32–55 years). Patients had received 4–6 prior lines of therapy, including cyclophosphamide (CYC, with median cumulative dose of 80 g) and steroids in every case, and rituximab in 4 cases. Stem cell source was peripheral blood in every case; CD34-selection was performed in 4 cases, mean CD34 + cell dose was 4.2 × 10 6 /kg (range 0.6–7.9 × 10 6 /kg). Conditioning regimen was CYC/ATG in 5 patients and CYC in 2 patients. Median follow-up was 86 months (range 1–204 months). Transplant-related mortality (TRM) occurred in 2 causes. All but one patient went into remission but 3 later relapsed at 6, 12 and 36 months, respectively, and required further treatment for disease control. At time of last clinical follow-up, 3 patients had drug-dependent partial response; 1 had drug-dependent complete remission and 1 had drug-free complete remission. Conclusions: Outcomes of HSCT for these heavily pre-treated AAV patients were variable. Only 1 patient achieved drug-free complete remission and TRM was observed in a quarter. Nevertheless, HSCT had the potential to stabilise AAV in patients who initially failed to respond to conventional therapies. These data do not support HSCT for advanced stage ANCA-positive vasculitis, although it may have a place as salvage treatment in otherwise refractory patients. As for other autoimmune diseases, HSCT may provide better outcomes when performed at early stage of disease. Overall, HSCT should only performed in clinical trial settings in experienced centres. Disclosure of Interest: None declared